The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1371/journal.pone.0000552
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Regimen Characteristics Associated with Self-Reported Nonadherence to Antiretroviral Therapy

Abstract: BackgroundNonadherence to antiretroviral therapy (ARVT) is an important behavioral determinant of the success of ARVT. Nonadherence may lead to virological failure, and increases the risk of development of drug resistance. Understanding the prevalence of nonadherence and associated factors is important to inform secondary HIV prevention efforts.Methodology/Principal FindingsWe used data from a cross-sectional interview study of persons with HIV conducted in 18 U.S. states from 2000–2004. We calculated the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 57 publications
4
40
2
3
Order By: Relevance
“…Overall, African Americans demonstrated lower rates of medication adherence over the course of the study, which is consistent with other studies examining ethnic differences in HIV medication adherence. [55][56][57] Results of previous studies assessing racial differences in HIV medication adherence have focused on socioeconomic factors that may moderate this relationship. However, there is more recent evidence to suggest that these factors alone do not eliminate disparities between racial groups on medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, African Americans demonstrated lower rates of medication adherence over the course of the study, which is consistent with other studies examining ethnic differences in HIV medication adherence. [55][56][57] Results of previous studies assessing racial differences in HIV medication adherence have focused on socioeconomic factors that may moderate this relationship. However, there is more recent evidence to suggest that these factors alone do not eliminate disparities between racial groups on medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…12 Knobel et al 13 found that only 33% of patients in their study were able to maintain an adherence level of at least 90% and in a study by Shuter et al, 7 patients experienced an average adherence rate of 73%. Several factors can impact a patient's adherence and persistence with antiretroviral therapy, including relationship with/trust in provider, 14 lack of social support, 14,15 regimen complexity, 16,17 and misunderstanding of the disease and drug treatment. 18 To address these barriers to adherence, select pharmacies have implemented specialized services for HIV patients within traditional community pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The underlying causes of these disparities are unclear but are probably manifold. One potential factor that has not been well studied is the role of communication barriers between patients and providers.…”
Section: Introductionmentioning
confidence: 99%